As vozes que recriaram as Áfricas: a intelectualidade de Kwame Nkrumah - Lopes, Victor De Carli (2019)
Mid-twentieth-century Africa had been fertile ground for an ambitious intellectual production. The domino effect of political independencies has brought a uncertainty atmosphere concerning the direction the continent would take, opening the way for the circularity of ideas that tensed the struggle for independence and future projections backed by African perspectives with the obstacles imposed by the colonization and neocolonialism. In this sense, the present dissertation analysis the role of the intellectuality of Kwame Nkrumah in this conjuncture, a representative choice given his notoriety in gaining independence in sub-Saharan Africa in Ghana (1957) and becoming its first Head of State. The author's philosophy will be analyzed through the concepts of African liberation, Pan-Africanism, neocolonialism and socialism, concepts which he was one of the main advocate and one of the most successful philosophers in reframing and fixing this contents. More than a mere epiphenomenon of his temporality, Nkrumah's utterances influenced the reality around him. From the analysis of his context, his texts and the author, this essay addresses the need to understand how the concepts appropriate by the Ghanaian author were related to his context. Thus, it is a constitutive part of this paper the effort to understand colonization and its consequences, the conceptualization of intellectuality and its epistemicide implications on the peripheral thinking and the construction of an interpretation that allows the author's concepts to be analyzed in his own words, using his own words and his main writings, Africa Must Unite and Neocolonialism, and others that allow the creation of a textual corpus. Finally, this work sums up to so many others stimulated by Brazilian Law 10,639/03 related by the production of content that discuss and value for the Afro-Brazilian and African history and culture.